Skeletal Anchorage Systems: A Narrative Review of Biomechanical Considerations for Predictable Orthodontic Tooth Movement with Maxillary and Mandibular Distalisation - Ramesh Carmel; Vincy Antony; Muhammed Shaloob; Sinjimol Thomas; Indu Nambiar (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
In recent years, skeletal anchorage systems have become an integral component of orthodontic biomechanics. They provide a reliable source of anchorage that is independent of the dentition, thereby improving the efficiency of distalisation with better control and reduced dependence on patient compliance. The present narrative review focuses on the biomechanical principles underlying skeletal anchorage-assisted distalisation. In particular, it examines the relationship between force vectors and the centre of resistance of the dental arches. Tooth movement depends largely on the point of force application relative to this centre, which determines whether the movement is primarily translational or accompanied by rotational changes, such as clockwise or counterclockwise rotation of the occlusal plane. Several skeletal anchorage options are available, including infrazygomatic crest mini-implants, buccal shelf screws, interradicular mini-implants, and palatal mini-implants. Each provides specific biomechanical advantages depending on the clinical situation. Maxillary and mandibular distalisation present distinct anatomical and biomechanical challenges, often requiring individualised force system design. Careful control of force magnitude, direction, and vector position allows predictable en masse distalisation. This approach also helps maintain incisor torque, vertical dimension, and occlusal stability. With appropriate planning, skeletal anchorage systems can be used to manage sagittal discrepancies in both camouflage and presurgical orthodontic treatment, offering better control and greater efficiency than conventional anchorage methods.